Strategi Produktivitas Lahan Persawahan dalam Mendukung Swasembada Pangan di Kabupaten Kerinci - yanto, Habri; Arsa, Muhammad; Roghib, Fadwa (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This study aims to see the productivity of rice fields in Kerinci district to formulation the productivity of rice fields in Kerinci district and the factors that influence the productivity of rice fields in Kerinci district. The study uses qualitative and quantitative research approaches. Qualitative research is used to collect data related to the development of rice fields and factors that influence the productivity of rice fields. Quantitative research is used to see the influence of factors that influence the productivity of rice fields in Kerinci district. Data collection uses observation, interview, documentation and questionnaire distribution methods using 100 snowball sampling samples. The results of the study show that many unproductive rice fields in Kerinci district are located in Batang Merangin, Bukit Kerman, Danau Kerinci, Gunung Raya sub-districts. The influencing factors are natural resources, labor, capital and entrepreneurship. The contribution of the influence of the variable model is 70.5% while 29.5% is determined by variables not included in this study. Qualitatively, the causes of unproductive rice fields are influenced by natural resources, damaged irrigation, increases in labor wages and workers switching to working on plantations, increases in fertilizer prices and economically, plantation businesses are considered more profitable than businesses in rice fields.